The Initial Opening of the Drake Passage Occurred During ca. 62‐59 Ma - Gao, Liang (2025)
Although the Drake Passage has been considered a critical component of ocean circulation and climate, its initial opening age remains controversial due to the weak constraints on the paleoposition of the Antarctic Peninsula. The biotic impact of this initial opening indicates, for example, that land-mammal faunas probably stopped their gene flow between Antarctica and South America. Here, new zircon U‐Pb geochronological studies are conducted on the Barchans Islands, providing a critical age constraint on the paleopole (Latitude = 76.9°S, Longitude = 332.1°E, A95 = 5.9°) of the peninsula at ca. 59 Ma. Geochronological and paleomagnetic studies on Anagram Island and King George Island provide a new paleopole (Latitude = 77.4°S, Longitude = 23.5°E, A95 = 4.4°) of the Antarctic Peninsula at ca. 55 Ma. When combined with existing evidence, the initial separation between the Antarctic Peninsula and the Patagonian Andes is restricted to be between ca. 62 and 59 Ma, caused by the clockwise rotation of the Antarctic Peninsula. The separation induced the initial opening of the Drake Passage and the formation of the shallow proto‐Antarctic circumpolar current, as well as Paleocene global cooling.